Experience and Prospects of Financing Renewable Energy Projects in Ukraine - Trypolska, Galyna; Riabchyn, Oleksiy (International Journal of Energy Economics and Policy, 2022)
The study examined the experience of financing renewable energy projects in Ukraine. Renewable energy is one of the tools to enhance decarbonization and meet the obligations taken within the Association Agreement between Ukraine and the EU, and under the Paris Agreement. Ukraine has factors impeding the investments, resulting in a high cost of capital. Overall, there are five main options of financing theoretically available: lending, primarily with the aid of international financial institutions; funding of renewable energy projects by municipalities; voluntary associations of citizens; securities; irrevocable financial assistance. The future instruments include securities and a recently announced mechanism to finance renewable energy projects in the frame of the Green Deal. The most expansive spread option for funding renewable energy projects was lending with the help of international financial institutions. Due to the bilateral electricity market transition of Ukraine in 2019, Ukraine failed to found a model for sustainable financing of electricity from renewables, resulted in the accumulation of significant debt with the feed-in tariff payment. This fact hinders the planned and potential future investments until a sustainable model of financing is found.